Enhancing Brand Equity Through Sustainable Tourism Marketing: A Study on Home-Stays in Malaysia - Zain ul Abedin Janjua; Gengeswari Krishnapillai; Mobashar Rehman (Asian Academy of Management Journal, 2023)
This study examined the antecedent and consequent relationship between sustainable tourism, marketing, and brand equity in the Malaysian rural community-based homestays (RCBHs) perspective. A self-administered questionnaire method was employed to collect data. Homestay operators from three Malaysian states, namely Kuala Lumpur/Selangor, Pahang, and Pulau Pinang participated in the study. In order to test research hypotheses, a structural equation modelling approach was used. The findings of the study suggested that the antecedent (sustainable tourism marketing), the consequent (brand equity), and moderator (political support by local authorities) have a significant relationship. Additionally, it was found that sustainable tourism marketing (STM) promotes rural community-based tourism. As a branding tool for sustainable rural community-based tourism. This study provides a unique contribution to the tourism body of knowledge by introducing political support by local authorities (PLA) as a moderator in STM and brand equity relationship. RCBHs can employ tailor-made promotion policies for the development of homestay business brands; likewise, policymakers can apply undifferentiated promotion policies for the holistic expansion of sustainable homestay market.